Efektivitas Jus Daun Seledri Dan Rebusan Daun Seledri Terhadap Tekanan Darah Pada Lansia Penderita Hipertensi Di Kampung Coblong Rt 005/Rw 001 Desa Sukagalih Tahun 2023 - Yusup Sopian; Emi Yuliza; Irma Herliana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hypertension is a health problem that often occurs in society. Uncontrolled hypertension can trigger degenerative diseases such as heart disease and kidney failure. One therapy used to lower blood pressure is celery leaf therapy. To determine the effectiveness of celery leaf juice and boiled celery leaves on blood pressure in elderly people with hypertension. This type of quantitative research is a Quasi Experimental design with Two Group pretest – posttest Control Group. The sampling technique used simple random sampling with a sample size of 32 people. The instruments in this study used a tensimeter, stethoscope, and observation sheet. Research results using the Wilxocon test and Mann Whitney U Test showed that the results of the analysis of celery leaf juice had a sig value of systolic ρ↑alue= 0.000≤α 0.05 and diastolic ρ-νalue = 0.000≤0.05. The results of the analysis of boiled celery leaves showed a sig value of systolic ρ-νalue = 0.000≤α 0.05 and ρ-νalue diastolic = 0.000≤0.05, meaning that celery leaf juice and celery leaf decoction are effective for blood pressure in elderly people suffering from hypertension. Celery Leaf Juice and Celery Leaf Infusion are Effective for Blood Pressure in Elderly People with Hypertension